Construction and Application of Integrated Diagnosis and Treatment System for Mycoplasma Pneumoniae Pneumonia in Children: A Regional Perspective - Jin, Hua; Wang, Zheng; Ta, Fujian; Zhang, Wuqiong; Wei, Wei; Yuan, Jinhua; Sun, Aimin; Zhao, Qian; Wang, Ruorui; Lu, Baoxian; Liu, Jialin (Transactions on Materials, Biotechnology and Life Sciences, 2024)
This paper aims to explore the construction and application of an integrated diagnosis and treatment system for Mycoplasma pneumoniae pneumonia (MPP) in children within a specific region. MPP is a common respiratory infection among children, posing challenges in diagnosis and uncertainty in treatment outcomes. By integrating modern technologies and interdisciplinary medical resources, this paper proposes a comprehensive system aimed at enhancing diagnostic accuracy, personalized treatment effects, and optimizing the efficiency of medical resource utilization. Through theoretical discussion, methodological descriptions, and practical case analyses, the paper demonstrates the system’s practical application and potential for future development.